Problem Posing Method In Establishing Students' Creative Thinking Ability In Islamic Education Subjects - Abizard Rafli Asrafzani; Moch. Charis; Asrori Asrori; Gamal Abdul Nasir Zakaria (At-Tarbiyat, 2022)
The problem posing method in shaping students' creative thinking skills in PAI subjects at SMKN 12 Surabaya, this is the title and purpose of this research. This study uses qualitative research methods or types of descriptive research. The results of the implication of the problem posing method in shaping students' creative thinking skills in PAI subjects at SMKN 12 Surabaya are going very well, this is based on observations and learning activities where students are required to make questions that are in harmony with the material provided. For this reason, students of SMKN 12 Surabaya became the subject of research. while the object of this research is the ability to think creatively in which there is a cognitive domain of students who develop knowledge and information in students' intellectual skills. By using the problem posing method, students have the ability to think creatively in accordance with what Johnson said, it will become a habit of mind that is trained with intuition, activates imagination, and reflexes will generate ideas. There are supporting factors, namely curiosity that appears more inclined to each question that is presented to make students able to improve their creative thinking skills and for the inhibiting factor students are afraid to answer because they are not sure of the answer.